2019
DOI: 10.1186/s12936-019-2660-y
|View full text |Cite
|
Sign up to set email alerts
|

Swarms of the malaria vector Anopheles funestus in Tanzania

Abstract: BackgroundAnopheles funestus mosquitoes currently contribute more than 85% of ongoing malaria transmission events in south-eastern Tanzania, even though they occur in lower densities than other vectors, such as Anopheles arabiensis. Unfortunately, the species ecology is minimally understood, partly because of difficulties in laboratory colonization. This study describes the first observations of An. funestus swarms in Tanzania, possibly heralding new opportunities for control.MethodUsing systematic searches by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 42 publications
1
32
1
Order By: Relevance
“…Swarms usually occur at approximately the same time, usually at sunset, and repeatedly at same locations throughout the year [47]. Studies done in Burkina Faso and Tanzania have shown that Anopheles mosquito swarms can be located and targeted, and are effective in reducing overall mosquito density [21][22][23] Modified mosquitoes This intervention refers to alterations of mosquito genes or physiology for the purpose of reducing their competence in diseases transmission. The modified mosquitoes are released into the environment so that they can interbreed with the wild mosquitoes and, depending on the trait they carry, either reduce the density of malaria vectors or replace its population with mosquitoes unable to transmit the pathogen.…”
Section: Intervention Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swarms usually occur at approximately the same time, usually at sunset, and repeatedly at same locations throughout the year [47]. Studies done in Burkina Faso and Tanzania have shown that Anopheles mosquito swarms can be located and targeted, and are effective in reducing overall mosquito density [21][22][23] Modified mosquitoes This intervention refers to alterations of mosquito genes or physiology for the purpose of reducing their competence in diseases transmission. The modified mosquitoes are released into the environment so that they can interbreed with the wild mosquitoes and, depending on the trait they carry, either reduce the density of malaria vectors or replace its population with mosquitoes unable to transmit the pathogen.…”
Section: Intervention Descriptionmentioning
confidence: 99%
“…Several complementary vector control interventions are currently being discussed as possible candidates to accelerate the malaria elimination efforts [12]. Examples include: (a) larval source management (LSM), including larviciding and environmental management [13,14], (b) topical repellents for personal protection [15,16], (c) mass drug administration with endectocides such as ivermectin [17,18], (d) use of mosquito modification techniques, either to suppress or replace vector populations [19,20], (e) outdoor targeting of male mosquitoes through insecticide-spraying of mosquito swarms [21][22][23], (f ) housing improvement measures such as better window screening and improved house designs [24][25][26], (g) spatial repellents able to protect multiple individuals over wide areas [27,28], (h) attractive toxic sugar baits targeting sugar-seeking mosquitoes [29,30], and (i) mosquito-killing fungal spores and toxins [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Community participation is considered essential for attaining an effective control of disease vectors [19], and multiple studies attest to the importance of enrolling local residents in campaigns against mosquitoes in particular [20][21][22][23][24]. Unfortunately, these studies provide limited information on the factors that motivate local communities to become actively involved in these interventions, and the question of which particular expectations and considerations drive public participation remains as a result underinvestigated.…”
Section: Introductionmentioning
confidence: 99%
“…Community participation is considered essential for attaining an effective control of disease vectors [19], and multiple studies attest to the importance of enrolling local residents in campaigns against mosquito vectors in particular [20][21][22][23][24]. Unfortunately, these studies provide limited information on the factors that motivate local communities to become actively involved in health programmes, and the question of which particular expectations and considerations drive public participation remains as a result under-investigated.…”
Section: Introductionmentioning
confidence: 99%